RETINAL MICROVASCULAR CHANGES IN PATIENTS WITH ACUTE LEUKEMIA. Issue 9 (September 2022) - Cicinelli, Maria V.; Mastaglio, Sara; Menean, Matteo; Marchese, Alessandro; Miserocchi, Elisabetta; Modorati, Giulio; Bernardi, Massimo; Ciceri, Fabio; Bandello, Francesco
Abstract : Supplemental Digital Content is Available in the Text. In this longitudinal study, patients with acute leukemia in the active phase had reduced vessel density, increased capillary diameter, and lower fractal dimension on optical coherence tomography angiography than healthy eyes, which correlated with bone marrow function failure. The retinal perfusion improved with disease remission. Abstract : Purpose: To evaluate the retinal circulation in patients with active acute leukemia, to correlate the perfusion metrics with systemic laboratory values, and to assess the vascular perfusion after leukemia remission. Methods: Longitudinal study of 22 eyes from 12 patients with acute leukemia; healthy eyes were recruited as control subjects. All patients underwent optical coherence tomography angiography at baseline. Optical coherence tomography angiography was repeated in case of morphologic leukemia remission. Results: Patients' age ranged from 37 to 74 years. All participants had a 20/20 vision. In all leukemic eyes, optical coherence tomography angiography detected vascular alterations in the macula and the peripapillary region. Vessel density values in the superficial capillary plexus were lower in patients with leukemia than control subjects (46.8 ± 3.6 vs. 49.2 ± 2%, P = 0.08), irrespective of the presence of leukemic retinopathy (7 eyes, 32%). Lower vessel density was associated with lower white blood cells ( P = 0.09) and lower platelets ( P = 0.001). Reappearance of small capillaries, increase in vessel density, reduction in vessel diameter, and increase in fractal dimension were seen after remission. Conclusion: Subclinical, reversible reduction in vessel density and complexity on optical coherence tomography angiography occurs in patients with active acute leukemia and is presumably associated with bone marrow function failure. Further studies are warranted to explore its functional and prognostic significance.